KONSELING KELOMPOK BERBASIS NILAI-NILAI ISLAM UNTUK MENINGKATKAN KEJUJURAN SISWA (Studi Kasus di SMP-IT Masjid Syuhada Yogyakarta) - Yusuf Hasan Baharuddin (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2016)
The research is aimed to measure the effectiveness of Islamic values used as a material in group counseling service in the school to increase the honesty of students at SMP-IT Masjid Syuhada Yogyakarta. The research method used is one group pre-test and post-test design experiment involving eight students of SMP-IT Masjid Syuhada. The research subject is chosen from the scale of the lowest honesty and based on the result of discussion among the researcher, the school counselor and the master of the class. The data are collected by using the scale of students’ honesty (ri= 0,367 – 0,729 α= 0,810 ), questionnaire, observation, and interview. The data analysis technique used is wilcoxon signed ranks test.The result of wilcoxon signed ranks test shows different score of the research subject’s (the students) honesty level before and after joining the group counseling service based on Islamic values (manipulation), Z = -2,232 and p-value = 0,026 (p-values < 0,050. The practical nuance of Islamic values supports the research subject in understanding and practicing the teaching got from their study and interaction with their parents and other people in their daily life. It can be concluded from the research that group counseling based on Islamic values can increase the students’ honesty, so it can be used to develop the counseling service in the school especially for the students with low level of honesty.